2019
DOI: 10.1016/j.cyto.2018.07.018
|View full text |Cite
|
Sign up to set email alerts
|

Whole-body cryotherapy (−110 °C) following high-intensity intermittent exercise does not alter hormonal, inflammatory or muscle damage biomarkers in trained males

Abstract: The results of this study suggest that the postulated physiological mechanisms by which WBC is proposed to improve recovery, i.e. reductions in inflammation and muscle damage, may not be accurate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
32
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(33 citation statements)
references
References 43 publications
1
32
0
Order By: Relevance
“…The response of these therapies is depended on an applied kind of exercise, its duration, frequency, intensity and other factors: such body composition, gender and environmental conditions ( Costello et al, 2015 ; Stephens et al, 2017 ). Recently published papers revealed that these two cold therapies used after high-intensity exercise, may not always bring significant and beneficial changes in muscle damage markers compare to other recovery methods ( Chan et al, 2016 ; Krueger et al, 2018 ). Still, the review written by Rose and colleagues has shown that the application of WBC following an intensive exercise had an analgesic effect and improved physical performance in 71% of the analyzed studies.…”
Section: Introductionmentioning
confidence: 99%
“…The response of these therapies is depended on an applied kind of exercise, its duration, frequency, intensity and other factors: such body composition, gender and environmental conditions ( Costello et al, 2015 ; Stephens et al, 2017 ). Recently published papers revealed that these two cold therapies used after high-intensity exercise, may not always bring significant and beneficial changes in muscle damage markers compare to other recovery methods ( Chan et al, 2016 ; Krueger et al, 2018 ). Still, the review written by Rose and colleagues has shown that the application of WBC following an intensive exercise had an analgesic effect and improved physical performance in 71% of the analyzed studies.…”
Section: Introductionmentioning
confidence: 99%
“…They observed also reduced CRP-levels 24 h after one session of WBC compared to passive recovery in equally trained participants. In contrast to these findings, the results of the recent Krueger et al study [23] have shown that WBC following high-intensity intermittent exercise did not alter hormonal, inflammatory or muscle damage biomarkers in trained males. Costello reported that there was no significant change in pain measurements during recovery with WBC [24].…”
Section: Introductionmentioning
confidence: 65%
“…The WBC method is based on providing the total contact of the patient's skin surface with a cryogenic gas. With a contact duration of up to 3 minutes and a gas temperature of less than 140 K, the WBC procedure provides a number of positive effects that are used in treatment practice [11,12]. The most demonstrative and controlled sign of the WBC effectiveness is the duration of analgesic action, which can last 6-8 hours [7].…”
Section: Historic Referencementioning
confidence: 99%
“…Under actual conditions, the WBC procedures in installations with a minimum temperature of 160 K (À110°C) do not ensure the constancy of the gas temperature, so the BS surface temperature after the procedure is much higher than the calculated one and is 15-20°C [24]. Such a temperature on the surface of the skin can be obtained using water baths with a temperature of 8°C; therefore, the doubts of some authors [11,18,25] on the advisability of using cryogenic technologies are fully justified.…”
Section: Selecting Optimal Gas Temperature In the Wbc Zonementioning
confidence: 99%